2020
DOI: 10.1242/dev.179325
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal stem cells: insights into maintaining and regenerating the skeleton

Abstract: Skeletal stem cells (SSCs) generate the progenitors needed for growth, maintenance and repair of the skeleton. Historically, SSCs have been defined as bone marrow-derived cells with inconsistent characteristics. However, recent in vivo tracking experiments have revealed the presence of SSCs not only within the bone marrow but also within the periosteum and growth plate reserve zone. These studies show that SSCs are highly heterogeneous with regard to lineage potential. It has also been revealed that, during di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 94 publications
0
49
0
Order By: Relevance
“…Here, we reported, for the first time, that AC also houses a class of Col2+ progenitors. Interestingly, we found that Col2+ cells in AC are similar to Pthrp+ cells 30 and Col2+ cells 3,31 in GP, and few can differentiate into adipocytes in vitro . Most interestingly, Col2+ in GP has a stronger osteogenic and chondrogenic differentiation ability than that in articular chondrocytes and BMSCs.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Here, we reported, for the first time, that AC also houses a class of Col2+ progenitors. Interestingly, we found that Col2+ cells in AC are similar to Pthrp+ cells 30 and Col2+ cells 3,31 in GP, and few can differentiate into adipocytes in vitro . Most interestingly, Col2+ in GP has a stronger osteogenic and chondrogenic differentiation ability than that in articular chondrocytes and BMSCs.…”
Section: Discussionmentioning
confidence: 76%
“…They are generally defined as self-renewing cells with the “trilineage” potential to differentiate into chondrocytes, osteoblasts and adipocytes. To date, there are three types of SSCs depending on their location: bone marrow-derived SSCs, GP SSCs (a cartilaginous structure separating the primary and secondary ossification centers in growing bones) and perichondrial/periosteal SSCs (the connective tissue surrounding bone) 3,18 . Previous studies have revealed that Col2+ cells in bone marrow, GP and perichondrial/periosteal behave as SSCs 3,29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain the findings in our study that osteoblasts may use different types of scaffolds for bone deposition during the formation of the epiphyseal bone plate. In this way, it is well known that osteoblasts can respond differently to stimuli depending on the bone compartment where they are located [ 33 ]. It has been reported that osteoblasts at the metaphyseal side of the growth plate radically change the mode of bone deposition to form a proper horizontal bone plate after surgical excision of the growth plate and subsequent reimplantation in the inverted orientation [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on the molecular identity of periosteal progenitors that contribute to fracture callus have used lineage tracing to identify a number of non-unique genes that mark this population [20]. Earlier work demonstrated high GFP reporter expression in periosteal cells of 3.6Col1a1-GFP mice and showed that 3.6Col1a1 marks cells of the osteoblast lineage [21].…”
Section: Introductionmentioning
confidence: 99%